Binaural Pitch Fusion: Binaural Pitch Averaging in Cochlear Implant Users With Broad Binaural Fusion. Issue 6 (November 2020) - Oh, Yonghee; Reiss, Lina A. J.
Abstract : Objectives: Individuals who use hearing aids (HAs) or cochlear implants (CIs) can experience broad binaural pitch fusion, such that sounds differing in pitch by as much as 3 to 4 octaves are perceptually integrated across ears. Previously, it was shown in HA users that the fused pitch is a weighted average of the two monaural pitches, ranging from equal weighting to dominance by the lower pitch. The goal of this study was to systematically measure the fused pitches in adult CI users, and determine whether CI users experience similar pitch averaging effects as observed in HA users. Design: Twelve adult CI users (Cochlear Ltd, Sydney, Australia) participated in this study: six bimodal CI users, who wear a CI with a contralateral HA, and six bilateral CI users. Stimuli to HA ears were acoustic pure tones, and stimuli to CI ears were biphasic pulse trains delivered to individual electrodes. Fusion ranges, the ranges of frequencies/electrodes in the comparison ear that were fused with a single electrode (electrode 22, 18, 12, or 6) in the reference ear, were measured using simultaneous, dichotic presentation of reference and comparison stimuli in opposite ears, and varying the comparison stimulus. Once the fusion ranges were measured, the fused binaural pitch of a reference-pair stimulus combination was measured by finding a pitch match to monaural comparison stimuli presented to the paired stimulus ear. Results: Fusion pitch weighting in CI users varied depending on the pitch difference of the reference-pair stimulus combination, with equal pitch averaging occurring for stimuli closer in pitch and lower pitch dominance occurring for stimuli farther apart in pitch. The averaging region was typically 0.5 to 2.3 octaves around the reference for bimodal CI users and 0.4 to 1.5 octaves for bilateral CI users. In some cases, a bias in the averaging region was observed toward the ear with greater stimulus variability. Conclusions: Fusion pitch weighting effects in CI users were similar to those observed previously in HA users. However, CI users showed greater inter-subject variability in both pitch averaging ranges and bias effects. These findings suggest that binaural pitch averaging could be a common underlying mechanism in hearing-impaired listeners. Abstract : Supplemental Digital Content is available in the text.